Contrast-Enhanced Mammography Accuracy in Assessing Preoperative Breast Tumor Size - M. Balbino; A. Ancona; F. Masino; S. Suriano; S. Cantore; M. Montatore; G. Guglielmi (Вестник рентгенологии и радиологии)
Background. Breast cancer is a leading type of cancer in women. Imaging techniques (ultrasound, mammography, and magnetic resonance imaging (MRI)) play a crucial role in tumor detection and evaluation. The last emerging technique is contrast-enhanced mammography (CEM) which provides both morphological and functional information.Objective: to evaluate CEM accuracy in measuring breast tumor lesions. Material and methods. The study involved 69 patients followed by the Breast Unit from January 2018 to September 2023. Breast tumor dimensions measured in CEM in the pre-operative stage by three experienced radiologists were compared to the dimension obtained at the histological examination, the current gold standard in assessing tumor size. Results. We observed a slight overestimation by CEM compared to histology, with a difference between the two measurements not more than 10 mm. CEM underestimated the dimensions in 12 of 69 cases. Conclusion. The study demonstrated excellent CEM accuracy in preoperative assessment of breast tumors, consistent with previous findings in the literature. CEM could prove to be a valid and safer alternative to MRI in preoperative breast tumor measuring.